Circular RNAs hsa_circ_0000479 in peripheral blood mononuclear cells as novel biomarkers for systemic lupus erythematosus. (2nd April 2020) - Luo, Qing; Zhang, Lu; Fang, Le; Fu, Biqi; Guo, Yang; Huang, Zikun; Li, Junming
Abstract: Circular RNAs (circRNAs) are a class of non-coding RNAs that play a crucial role in diagnosis and prognosis of systemic lupus erythematosus (SLE). However, circRNAs expression profiling in SLE from different reports are different. In this study, 11 circRNAs (hsa_circ_0000479, hsa_circ_0002316, hsa_circ_0000317, hsa_circ_0082688, hsa_circ_0082689, hsa_circ_0087798, hsa_circ_0008529, hsa_circ_0000787, hsa_circ_0021727, hsa_circ_0000175, and hsa_circ_0003694) which were found to be significantly up-regulated in both peripheral blood mononuclear cells (PBMCs) from SLE patients in our previous study, and T cells from SLE patients in previous literature, were chosen for validation by quantitative reverse transcription–polymerase chain reaction in PBMCs from 50 new-onset SLE patients, 24 new-onset rheumatoid arthritis (RA) patients, 24 new-onset ankylosing spondylitis (AS) patients, and 45 age- and sex-matched healthy controls (HC). The results validated that PBMCs hsa_circ_0000479, hsa_circ_0082688, and hsa_circ_0082689 were increased, while hsa_circ_0000175 was significantly decreased in SLE patients than that in RA patients, AS patients, and HC. The correlation analysis of these confirmed differentially expressed circRNAs showed that hsa_circ_0000479 was associated with C3 level and treatment, hsa_circ_0082688 was associated with anti-dsDNA level, hsa_circ_0082689 was associated with anti-dsDNA level, anti-nuclesome frequency and treatment. Receiver operating characteristic curve anaylsis suggested that hsa_circ_0000479 has significant value in distinguishing SLE from AS patients, RA patients, and HC (AUC = 0.825, p  < .001). Moreover, the hsa_circ_0000479-anti-dsDNA combination model could effectively discriminate the SLE group and the control groups (RA + AS + HC), with a sensitivity of 86.00% (43/50), a specificity of 100.00% (93/93), and an accuracy of 95.10% (136/143). This study suggested that hsa_circ_0000479 in PBMC and hsa_circ_0000479-anti-dsDNA combination model may serve as potential biomarkers for SLE diagnosis and evaluation of therapeutic effect.